Supplemental feeding and nutrition education to reduce stunting in indonesian toddlers - the DASHAT programme: Fortified Milk to Prevent Stunting - Khomsan, Ali; Rifayanto, Rania Permata; Firdausi, Alya; Adha, As Syaffa Ammalia; Herdiana, Eka; Wibowo, Yulianti; Nuranti, Afifah; Afrilda, Yusna; Hasanah, Nurmala (Progress in Nutrition, 2024)
Background and aim: Dapur Sehat Atasi Stunting (DASHAT) is a flagship programme of the Indonesian National Population and Family Planning Board (BKKBN) to reduce stunting prevalence. Considering the increased prevalence of stunting among Indonesian toddlers, the objective of the study was to evaluate the improvement in the nutritional status, food diversity, and nutrient adequacy of children participating in the DASHAT programme. The study also intended to analyse the nutrition knowledge of mothers of toddlers. Methods: A pre-post experimental design study without control was conducted in Karawang, Indonesia from August 2022 to December 2022. The study involved the participation of approximately 85 toddlers who were underweight, severely underweight, stunted and severely stunted, along with their mothers. Nutrition education was provided for mothers, while supplementary feeding (meals and fortified milk) was given to toddlers, 3 times a week for 3 months. Paired t-test was used to compare baseline and postintervention data. Results: Results indicate a significant increase (p